Effectiveness of novel, lower cost molecular human papillomavirus‐based tests for cervical cancer screening in rural china. Issue 6 (19th October 2015) - Valdez, Melissa; Jeronimo, Jose; Bansil, Pooja; Qiao, You‐Lin; Zhao, Fang‐Hui; Chen, Wen; Zhang, Xun; Kang, Le‐Ni; Paul, Proma; Bai, Ping; Peck, Roger; Li, Jing; et al.
Abstract : This study examined the efficacy of the Onco E6 ™ Cervical Test, care HPV™ and visual inspection with acetic acid (VIA) in identifying women at risk for cervical cancer and their capability to detect incident cervical precancer and cancer at 1‐year follow‐up. In a population of 7, 543 women living in rural China, women provided a self‐collected and two clinician‐collected specimens and underwent VIA. All screen positive women for any of the tests, a ∼10% random sample of test‐negative women that underwent colposcopy at baseline, and an additional ∼10% random sample of test‐negative women who did not undergo colposcopy at baseline ( n  = 3, 290) were recruited. 2, 904 women were rescreened 1 year later using the same tests, colposcopic referral criteria, and procedures. Sensitivities of baseline tests to detect 1‐year cumulative cervical intraepithelial neoplasia Grade 3 or cancer (CIN3+) were 96.5% and 81.6% for care HPV™ on clinician‐collected and self‐collected specimens, respectively, and 54.4% for Onco E6 ™ test. The Onco E6 ™ test was very specific (99.1%) and had the greatest positive predictive value (PPV; 47.7%) for CIN3+. Baseline and 1‐year follow‐up cervical specimens testing HPV DNA positive was sensitive (88.0%) but poorly predictive (5.5–6.0%) of incident CIN2+, whereas testing repeat HPV16, 18 and 45 E6 positive identified only 24.0% of incident CIN2+ but had a predictive value of 33.3%. This study highlights the different utility of HPV DNA and E6 tests, the former as a screening and the latter as a diagnostic test, for detection of cervical precancer and cancer. Abstract : What's new? Low‐cost technologies for the detection of high‐risk human papillomavirus (hrHPV) types are of particular interest for use in cervical cancer screening in developing countries. Promising technologies include those that are capable of detecting the HPV E6 oncoprotein or hrHPV DNA. This evaluation of women in rural China shows that tests for E6 and HPV DNA differ in their detection performance yet are complementary in cervical cancer assessment. HPV DNA detection showed superior screening performance, because of its high sensitivity and negative predictive value. HPV E6 detection performed better in diagnosis, because of its specificity and positive predictive value.